A left-handed circularly polarized luminescent composite photonic film and its preparation method and application
By functionally modifying hydroxypropyl cellulose and doping luminescent materials, combined with spiral co-assembly and ultraviolet cross-linking technology, a left-circular polarized luminescent composite photon film was prepared, solving the monotonous luminescent mode and expensive material in the existing technology. These problems have achieved multi-color circular polarization luminescence and high mechanical properties, which are suitable for modern anti-counterfeiting needs.
Patent Information
- Application Number
- CN202410107046.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-25
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-01-25
AI Technical Summary
The existing luminescence certification technology has problems such as monotonous luminescence mode, expensive monomer materials, cumbersome synthesis processes, high cost, and application scenarios for material safety limitations, which are difficult to meet modern anti-counterfeiting needs.
Hydroxypropyl cellulose (HPC) is functionally modified by methacrylic anhydride (MA) and doped with luminescents such as N-(3-(phenylamino)allylene)aniline hydrochloride (PA) Derivatives, a left-circular polarized light-emitting composite photon film was prepared using spiral co-assembly and ultraviolet cross-linking technology.
It realizes bright full-color structural color, structural color variation with humidity response, adjustable multi-color left-circular polarized light emission, with excellent mechanical flexibility, durability and adhesion, and is suitable for applications such as anti-counterfeiting pattern labels.
Smart Images

Figure CN118005966B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of material preparation, and in particular relates to a left-handed circularly polarized luminescent composite photonic film and a preparation method and application thereof. Background Art
[0002] The impact and harm of counterfeit products on human society are increasing. In 2022, the international trade value of counterfeit goods was about 991 billion US dollars. From ancient times to the present, a large number of open and secret anti-counterfeiting technologies have been developed, from the simplest anti-counterfeiting means such as graphics, watermarks and handwriting in ancient times to more advanced anti-counterfeiting measures such as electronic identification, product marking, and mechanical, chemical, physical and digital tools. For example, the uniqueness of electronic anti-counterfeiting technology helps to achieve highly secure anti-counterfeiting through reading devices and server connections. In addition, visualized optical readout strategies, such as luminous label technology, have become the most commonly used strategies to combat counterfeiting due to their simplicity, low cost and large-scale production as well as programmable optical signals.
[0003] However, current luminescent authentication technologies focus on using complex and stimulus-responsive luminescence modes to convey hidden information, such as multimode perovskite nanocrystals, phosphorescent afterglow materials, full-color quantum dots, and stable lanthanide luminescence. More profoundly, while ensuring UV-active photoluminescence, it is given a reflective color to show the integration of dual optical states. However, the monotonous luminescence mode of its commercial anti-counterfeiting materials limits the application of anti-counterfeiting, and simple single optical or even dual optical systems can no longer meet the current application needs of anti-counterfeiting. There is an urgent need to develop new luminescence modes and multi-level anti-counterfeiting materials to solve the bottleneck of physical anti-counterfeiting. In addition to the above reasons, there are also the following problems to be solved: 1) The expensive monomer materials and their cumbersome synthesis process increase the production cost; 2) The reflective color of the luminescent material is adjusted by changing the inherent chemical structure (a typical example is azobenzene or pyran compounds), which will inevitably change the fluorescence properties; 3) The safety of the material limits the application scenarios. Therefore, designing an ideal anti-counterfeiting technology with multi-level, new luminescence mode, low cost, non-destructive and environmentally friendly has become the most challenging topic. Summary of the invention
[0004] The purpose of the present invention is to provide a left-handed circularly polarized luminescent composite photonic film and its preparation method and application. Here, we functionalize hydroxypropyl cellulose (HPC) with methacrylic anhydride (MA) and then dope it with a luminophore such as N-(3-(phenylamino)allylidene)aniline hydrochloride (PA) derivative to solve the problems existing in the above-mentioned prior art. Based on the hydrogen bond network of HPC derivatives and the hydrogen bond force possessed by luminophores such as PA derivatives, the luminophore molecules can be evenly distributed in the HPC derivatives to ensure the uniform emission of the chiral photonic composite film. More importantly, HPC-MA / PA has photo-crosslinking ability, provides flexibility and plasticity, and the prepared chiral photonic materials can be used on different substrates. This research has opened up a new field for optical anti-counterfeiting label products, developing materials with strong left-handed circularly polarized light (L-CPL). These materials will promote the development of chiral symmetric luminescent materials based on cellulose photonic structures, and provide potential advantages for their application in wearable optoelectronic devices, polarization customized patterns, chiral medical imaging, enantiomeric synthesis and chiral sensing. The present invention prepares a representative left-handed circularly polarized luminescent composite photonic film, which exhibits bright full-color structural color, humidity-responsive structural color variation and adjustable multi-color left-handed circularly polarized light emission, and also has excellent mechanical flexibility, durability and adhesion.
[0005] In order to achieve the above object, the present invention adopts the following technical scheme:
[0006] One of the technical solutions is a left-handed circularly polarized luminescent composite photonic film, which is prepared by spiral co-assembly of methacrylated hydroxypropyl cellulose (HPC-MA) and a luminophore in the dark to form a chiral nematic structure, which is then cross-linked and polymerized by ultraviolet light under a photoinitiator and then dried.
[0007] The luminophore is a luminophore capable of achieving solid luminescence. The luminescent efficacy thereof is combined with HPC-MA to form a chiral nematic structure through spiral co-assembly to achieve circularly polarized luminescence. The luminophores of different fluorescent colors can be regulated to achieve full-band color circularly polarized luminescence. The luminophore is an N-(3-(phenylamino)allylidene)aniline hydrochloride derivative, a dye, a perovskite, and an aggregation-induced luminescence molecule, etc., preferably an N-(3-(phenylamino)allylidene)aniline hydrochloride derivative. The N-(3-(phenylamino)allylidene)aniline hydrochloride derivative is N-(3-(phenylamino)allylidene)-4-bromoaniline hydrochloride (PA-Br), PA-CF3, and PA-Bip, etc.; the dye is fluorescein, rhodamine, etc.; the perovskite is a metal halide perovskite, etc.; the aggregation-induced luminescence molecule is a tetraphenylethylene derivative, a hexaphenylthiole derivative, etc.
[0008] The photoinitiator is a photoinitiator having an active hydroxyl group, such as 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (photoinitiator 2959) and the like.
[0009] A left-handed circularly polarized luminescent composite photonic film, the preparation method of which comprises the following steps: uniformly dispersing methacrylated hydroxypropyl cellulose (HPC-MA), a luminophore and a photoinitiator in an organic solvent to obtain a precursor liquid with a certain HPC-MA content, uniformly forming a film from the precursor liquid by spin coating, first self-assembling in the dark to form a chiral nematic structure, then cross-linking and polymerizing under ultraviolet light, and finally drying to obtain a left-handed circularly polarized luminescent composite photonic film.
[0010] The methacrylated hydroxypropyl cellulose (HPC-MA) is prepared from hydroxypropyl cellulose (HPC) and methacrylic anhydride (MA), and the average molecular weight of the hydroxypropyl cellulose (HPC) is preferably 40,000.
[0011] The organic solvent is N,N-dimethylformamide (DMF).
[0012] The content of HPC-MA in the precursor liquid is 68wt%-72wt%; the mass ratio of the HPC-MA, the luminophore and the photoinitiator is 300-500:1:1, preferably 350-450:1:1, and more preferably 380-420:1:1.
[0013] The self-assembly time is more than 15 minutes; the UV light cross-linking time is more than 5 minutes.
[0014] Technical solution 2, a method for preparing a left-handed circularly polarized luminescent composite photonic film, comprising the following steps:
[0015] (1) Preparation of methacrylated hydroxypropyl cellulose: hydroxypropyl cellulose is uniformly dispersed in deionized water, vigorously stirred and methacrylic anhydride is added, and then sodium hydroxide solution is injected into the mixture, and stirred at room temperature for a certain period of time. The resulting suspension is heated to obtain a milky white colloidal precipitate, and then placed in a dialysis bag (preferably a dialysis bag with a molecular cutoff of 12000-14000) for dialyzing to remove small molecules, and freeze-dried to obtain methacrylated hydroxypropyl cellulose;
[0016] (2) Preparation of precursor liquid: methacrylated hydroxypropyl cellulose (HPC-MA), luminophore and photoinitiator are uniformly dispersed in an organic solvent to obtain a precursor liquid with a certain HPC-MA content;
[0017] (3) Preparation of left-handed circularly polarized luminescent composite photonic film: After centrifuging the precursor liquid in step (2) to remove bubbles, take an appropriate amount and drop it on a substrate, place the substrate with the precursor liquid on the support of a spin coater to form a uniform film by spin coating, and then stand it in a dark place for more than 15 minutes to self-assemble to form a chiral nematic structure, then use ultraviolet light for cross-linking polymerization for at least 5 minutes, and then dry it to obtain a left-handed circularly polarized luminescent composite photonic film.
[0018] In step (1), the ratio of hydroxypropyl cellulose to deionized water is 1 g:50 mL; the concentration of the sodium hydroxide solution is 5 mol·L -1 The mass ratio of hydroxypropyl cellulose, methacrylic anhydride and sodium hydroxide is 20.0:82.8:24.0. Sodium hydroxide solution is injected into the mixture, stirred at room temperature for 12 hours, and the resulting suspension is heated to 40-50°C and kept warm for 1 hour to obtain a milky white colloidal precipitate.
[0019] In step (2), the photoinitiator is a photoinitiator having an active hydroxyl group, such as 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (photoinitiator 2959), etc.; the organic solvent is N,N-dimethylformamide (DMF); the mass ratio of the HPC-MA, the luminophore and the photoinitiator is 300-500:1:1, preferably 350-450:1:1, and more preferably 380-420:1:1; the HPC-MA content in the precursor liquid (the amount of the luminophore and the photoinitiator added is small and can be ignored) is 68wt%-72wt%; the luminophore is an N-(3-(phenylamino)allylidene)aniline hydrochloride derivative, a dye, a perovskite and an aggregation-induced emission molecule, etc., preferably an N-(3-(phenylamino)allylidene)aniline hydrochloride derivative, and the preparation steps are as follows:
[0020] 1,1,3,3-tetramethoxypropane is added to an anhydrous ethanol solution of 4-X aniline, and then an appropriate amount of 36wt% concentrated hydrochloric acid is slowly added dropwise, stirred at room temperature for a certain period of time, filtered, washed with anhydrous ethanol, and dried to obtain N-(3-(phenylamino)allylidene)aniline hydrochloride derivative PA-X having fluorescent properties;
[0021] The molar ratio of the 1,1,3,3-tetramethoxypropane to the 4-X aniline is 1:2; X in the 4-X aniline is a substituent, such as a halogen element (preferably bromine), trifluoromethyl, phenyl, etc.; the amount ratio of the 1,1,3,3-tetramethoxypropane to concentrated hydrochloric acid is 1 mmol:1 mL; stirring at room temperature for 5 hours;
[0022] In step (3), the substrate is not limited in material, for example, it can be polytetrafluoroethylene (PTFE), wood, stainless steel sheet (metal), glass, resin (PET) and the like; the speed and time of the spin coater are set so that the precursor liquid is evenly spread on the substrate. For example, for 1 mL of precursor liquid, the spin coating speed is set to 60 r / min. -1 , the spin coating time is 3 minutes; the wavelength of the ultraviolet light is 365nm, and the power is 5W.
[0023] The third technical solution is the application of the above-mentioned left-handed circularly polarized luminescent composite photonic film and the left-handed circularly polarized luminescent composite photonic film prepared by the above-mentioned method in anti-counterfeiting pattern labels.
[0024] The present invention adopts a combination of spiral co-assembly and ultraviolet light cross-linking technology to prepare a hydroxypropyl cellulose composite photonic film, which exhibits high anti-counterfeiting and strong left-handed circularly polarized luminescence ability.
[0025] Using the spiral co-assembly strategy, an HPC-PA composite photonic film showing uniform optical distribution and strong left-handed circularly polarized luminescence is constructed on the film. The introduction of PA derivatives enables the composite film to exhibit high-brightness luminescence performance. In addition, the HPC solution (50%-70% by mass) exhibits a reflective color and becomes colorless after drying, which is not conducive to the application of solid photonic films. In order to solve the above problems, the present invention introduces methacrylic anhydride (MA) into HPC by grafting. On the one hand, MA modifies HPC through esterification reaction, retaining the responsive structural color; on the other hand, the modified HPC has the ability of photocrosslinking, which increases the plasticity of the physical form of the HPC-MA material. The composite film after photocrosslinking has a stable chemical structure and shows extremely excellent resistance to extreme environments. The strong adhesion effect of the high-concentration HPC-MA solution makes the film molding surface uneven. To this end, a spin coater is used to evenly distribute it on the substrate by spin coating. Finally, we obtained a hydroxypropyl cellulose composite film with strong left-handed circularly polarized luminescence and multi-color circularly polarized luminescence, and this hydroxypropyl cellulose optical film can be used for anti-counterfeiting labels. Here, the hydroxypropyl cellulose-derived luminescent material can simultaneously exhibit a unique combination of high luminescence asymmetry factor (0.51), high emission quantum yield (55.8%), strong left-handed circularly polarized luminescence and multi-color circularly polarized luminescence, and take into account the ability of flexibility and adhesion to achieve a higher level of communication applications. Bright photoluminescence and multi-mode integrated coding contribute to the device application of HPC. A representative strong left-handed circularly polarized luminescent photonic film was prepared using a convenient method, in which multi-color circularly polarized emission was achieved by adjusting PA derivatives with different substituents. This method is superior to the preparation of other anti-counterfeiting label materials, such as the existence of secondary pollution, incomplete optical properties, high cost, and unfavorable large-scale production applications.
[0026] The advantages and beneficial effects of the present invention are as follows:
[0027] By combining spiral co-assembly and ultraviolet light cross-linking technology, a hydroxypropyl cellulose composite photonic film with strong left-handed circularly polarized luminescence is constructed; a highly anti-counterfeiting and convertible multi-color circularly polarized luminescent composite film is prepared; the preparation process of this material is easy to operate and low-cost; the photonic composite film has polarization anti-counterfeiting function and an asymmetric induced photochemical system.
[0028] Sustainable hydroxypropyl cellulose was used as the matrix, and a multicolor circularly polarized luminescent photonic film was constructed by combining spiral co-assembly and ultraviolet light cross-linking technology; the methacrylic anhydride esterification reaction achieved the modification of the photonic film, homogeneous photo-cross-linking ability, and multicolor left-handed circularly polarized luminescence. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 : This is the appearance of the freeze-dried HPC-MA of Example 1;
[0030] Figure 2 : This is the fluorescence real image of PA-CF3, PA-Bip and PA-Br powders of Example 1 under 365nm ultraviolet light;
[0031] Figure 3 : The appearance of the HPC-MA / PA-Br precursor solution of Example 1 at different angles;
[0032] Figure 4 : The appearance of the HPC-MA / PA-Br precursor droplets of Example 1 applied on different substrates;
[0033] Figure 5 : The HPC-MA / PA-Br precursor solutions with different HPC-MA contents in Example 1 were subjected to spin coating, self-assembly and UV-crosslinking to prepare composite films with different colors (red, yellow, green, blue and purple) under natural light;
[0034] Figure 6 : The HPM-Br, HPM-CF3, and HPM-Bip films of Example 1 exhibit circularly polarized luminescence of different colors under 365nm ultraviolet light excitation;
[0035] Figure 7 : POM image of the HPM-Br membrane of Example 1;
[0036] Figure 8 : is the SEM image of the HMP-Br membrane of Example 1;
[0037] Fig. 9 : CD spectrum of the HMP-Br membrane of Example 1;
[0038] Fig.10 : is the reflection spectrum of the HMP-Br film of Example 1 at different angles;
[0039] Fig.11 : is the reflection spectrum of the HMP-Br film of Example 1 tested at different humidity levels for 10 cycles;
[0040] Fig.12 : Figures of the HMP-Br film of Example 1 under different polarized light sources, right-handed CPL (upper) and left-handed CPL (lower);
[0041] Fig.13 : The actual pictures of the HMP-Br membrane of Example 1 before and after being immersed in water for three months under 365nm ultraviolet light;
[0042] Fig.14 : The photoluminescence spectrum of the HMP-Br film of Example 1 when it receives opposite CPL excitation at a wavelength of 410 nm. DETAILED DESCRIPTION
[0043] The present invention will be further described below in conjunction with the embodiments and drawings.
[0044] Embodiment 1: A method for preparing a left-handed circularly polarized luminescent composite photonic film, comprising the following steps:
[0045] (1) 20 g of hydroxypropyl cellulose (HPC, average molecular weight 40000 g·mol -1 ) powder was evenly dispersed in 1000 ml of deionized water, stirred vigorously and 80 ml of methacrylic anhydride (MA) was added. -1 120 ml of 5M sodium hydroxide solution was injected into the mixture at a speed of 1.000 rpm. After the sodium hydroxide solution was completely added, the mixture was heated at room temperature at 400 r / min. -1 The suspension was heated in a water bath at 40°C for 1 hour to obtain a milky white colloidal precipitate. Finally, the precipitate was placed in a dialysis bag with a molecular cutoff of 12000-14000 and dialyzed for 5 days. After freeze drying, methacrylated hydroxypropyl cellulose (HPC-MA) was obtained. Figure 1 , HPC-MA appears as a white aerogel solid.
[0046] (2) Add 3 mmol 1,1,3,3-tetramethoxypropane to 25 mL anhydrous ethanol solution of 6 mmol 4-bromoaniline, slowly add 3 mL of 36 wt% concentrated hydrochloric acid at 20°C, and stir the reaction mixture at room temperature for 5 hours. After the reaction is completed, a large amount of precipitate is obtained by recrystallization. The precipitate is filtered and repeatedly washed with 50 mL of anhydrous ethanol. Finally, it is dried in a vacuum to obtain N-(3-(phenylamino)allylidene)-4-bromoaniline hydrochloride solid powder (PA-Br) with fluorescent properties. In addition, according to the same method, 4-bromoaniline is replaced with different monomers 4-trifluoromethylaniline and 4-aminobiphenyl to obtain two other N-(3-(phenylamino)allylidene)aniline hydrochloride derivatives PA-CF3 and PA-Bip. PA-CF3, PA-Bip and PA-Br powders show different fluorescent colors under 365 nm ultraviolet light, see Figure 2 .
[0047] (3) Disperse 17.5 mg of 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone (photoinitiator 2959) and 17.5 mg of N-(3-(phenylamino)allylidene)-4-bromoaniline hydrochloride solid powder (PA-Br) prepared in step (2) in 3.2 g of N,N-dimethylformamide (DMF). Perform ultrasonic treatment for 5 minutes to ensure uniform dispersion. Then, add 6.8 g of methacrylated hydroxypropyl cellulose (HPC-MA) prepared in step (1) to the aforementioned DMF mixed solution in batches to form a uniform dispersion, and obtain an HPC-MA / PA-Br precursor solution with an HPC-MA content of 68 wt%, the appearance of which is shown in FIG. Figure 3 The HPC-MA / PA-Br precursor solution exhibits angle-varying reflective color performance, showing different colors at different angles. It is then stored in a refrigerator at 2°C away from light.
[0048] (4) First, the HPC-MA / PA-Br precursor solution in step (3) was heated at 6000 r·min -1 Centrifuge at a speed of 1000 to remove bubbles. Take 2 mL of HPC-MA / PA-Br precursor and drop it on polytetrafluoroethylene (PTFE), wood, stainless steel sheet (metal), glass, resin (PET) and other substrates. Figure 4 , HPC-MA / PA-Br precursor solution showed strong adhesion on different substrates. 1 mL of HPC-MA / PA-Br precursor solution was dropped onto a 5 cm diameter polytetrafluoroethylene (PTFE) substrate, and the PTFE substrate with HPC-MA / PA-Br precursor solution was placed on the spin coater support and spun at 60 r·min. -1After the HPC-MA / PA-Br precursor solution was uniformly formed into a film, the film and the polytetrafluoroethylene substrate were placed in a 2°C refrigerator, kept away from light, and self-assembled for 15 minutes to form a chiral nematic structure. Finally, the film was photocrosslinked for 5 minutes using ultraviolet light with a power of 5W and a wavelength of 365nm. After natural air drying at room temperature, a red film was obtained under natural light (see Figure 5 The composite film (a) emits green circularly polarized light under 365nm ultraviolet light excitation (see Figure 6 ), abbreviated as HPM-Br.
[0049] The luminophore PA-CF3 prepared in step (2) was used to prepare an HPC-MA / PA-CF3 precursor solution with an HPC-MA content of 68 wt % according to the same steps as above, and further spin-coated, self-assembled and UV-crosslinked to obtain a composite film, referred to as HPM-CF3, which emits blue circularly polarized light under 365 nm UV excitation (see Figure 6 ).
[0050] The luminophore PA-Bip prepared in step (2) was used to prepare an HPC-MA / PA-Bip precursor solution with an HPC-MA content of 68 wt % according to the same steps as above, and further spin-coated, self-assembled and UV-crosslinked to obtain a composite film, referred to as HPM-Bip, which emits orange circularly polarized light (see Figure 6 ).
[0051] In order to realize full-color composite film, only the mass ratio of HPC-MA to DMF in the HPC-MA / PA-Br precursor solution in step (3) was adjusted. The amount of HPC-MA added was 6.9 g, 7.0 g, 7.1 g, and 7.2 g, respectively; the amount of DMF added was 3.1 g, 3.0 g, 2.9 g, and 2.8 g, respectively; the content of HPC-MA in the HPC-MA / PA-Br precursor solution was 69 wt%, 70 wt%, 71 wt%, and 72 wt%, respectively; the other steps remained unchanged, and finally composite films showing yellow, green, blue, and purple colors under natural light were obtained, as shown in FIG. Figure 5 .
[0052] The POM (Polarized Optical Microscope) image of the HPM-Br film shows birefringence, such as Figure 7 .
[0053] The SEM images of HMP-Br membranes show the Brinell structure formed by spiral stacking, such as Figure 8 .
[0054] The CD spectrum (circular dichroism spectrum) of HMP-Br membrane shows a very strong negative CD value, such as Fig. 9 .
[0055] The reflection spectrum of HMP-Br film at different angles shows that the wavelength gradually redshifts as the observation angle increases (15°-90°), such as Fig.10 .
[0056] The reflectance spectra of HMP-Br film tested at different humidity levels for 10 cycles are shown in Figure 2. Fig.11 When the HMP-Br film is dry (SR=0%), the color measured at 45° using a fiber optic spectrometer is green (reflection band is around 500nm). After being soaked (SR=60%), the color measured at 45° is red (reflection band is around 670nm). The reflectance spectrum of 10 cycles of dry and wet tests indicates that the HMP-Br film has reversible structural color changes under different humidity absorption.
[0057] Fig.12 Figure 2 shows the HMP-Br film under different polarized light sources, right-handed CPL (upper figure) and left-handed CPL (lower figure). Due to the chiral nematic structure of the film, selective reflection occurs.
[0058] The actual pictures of HMP-Br membrane under 365nm ultraviolet light before and after being immersed in water for three months are as follows Fig.13 The HMP-Br film can still emit bright fluorescence after being immersed in water for three months. The luminescence intensity of the HMP-Br film under 365nm ultraviolet light when it is not immersed (a) and the luminescence intensity after being immersed in water for three months (b) do not change significantly, indicating that the film has good water resistance and stability.
[0059] The photoluminescence spectrum of HMP-Br film when receiving opposite CPL excitation at 410nm wavelength is shown in Fig.14 , the luminescence asymmetry factor g is calculated by the formula lum =2(I L -I R ) / (I L +I R ), I L represents the photointensity under left-handed CPL, I R represents the photointensity under right-handed CPL, g lum =0.51.
[0060] The embodiments are preferred implementations of the present invention, but the present invention is not limited to the above-mentioned implementations. Any obvious improvements, substitutions or modifications that can be made by those skilled in the art without departing from the essential content of the present invention belong to the protection scope of the present invention.
Claims
1. A left-handed circularly polarized luminescent composite photonic film, characterized in that: The methacrylated hydroxypropyl cellulose and the luminophore are spirally co-assembled in the dark to form a chiral nematic structure, and then cross-linked and polymerized by ultraviolet light under a photoinitiator and then dried. The luminophore is an N-(3-(phenylamino)allylidene)aniline hydrochloride derivative; and the photoinitiator is a photoinitiator having active hydroxyl groups.
2. The left-handed circularly polarized luminescent composite photonic film according to claim 1, characterized in that: The preparation method comprises the following steps: uniformly dispersing methacrylated hydroxypropyl cellulose, a luminophore and a photoinitiator in an organic solvent to obtain a precursor liquid with a certain methacrylated hydroxypropyl cellulose content, uniformly forming a film from the precursor liquid by spin coating, first self-assembling in the dark to form a chiral nematic structure, then cross-linking and polymerizing under ultraviolet light, and finally drying to obtain a left-handed circularly polarized luminescent composite photonic film.
3. The left-handed circularly polarized luminescent composite photonic film according to claim 2, characterized in that: The methacrylated hydroxypropyl cellulose is prepared from hydroxypropyl cellulose and methacrylic anhydride; and / or The average molecular weight of the hydroxypropyl cellulose is 40,000; and / or The organic solvent is N,N-dimethylformamide; and / or The content of methacrylated hydroxypropyl cellulose in the precursor liquid is 68wt%-72wt%; and / or The mass ratio of the methacrylated hydroxypropyl cellulose, the luminophore and the photoinitiator is 300-500:1:1; and / or The self-assembly time is more than 15 minutes; the UV light cross-linking time is more than 5 minutes.
4. The left-handed circularly polarized luminescent composite photonic film according to claim 3, characterized in that: The mass ratio of the methacrylated hydroxypropyl cellulose, the luminophore and the photoinitiator is 350-450:1:
1.
5. The left-handed circularly polarized luminescent composite photonic film according to claim 4, characterized in that: The mass ratio of the methacrylated hydroxypropyl cellulose, the luminophore and the photoinitiator is 380-420:1:
1.
6. The method for preparing the left-handed circularly polarized luminescent composite photonic film according to any one of claims 1 to 5, characterized in that: The steps include: (1) Preparation of methacrylated hydroxypropyl cellulose: hydroxypropyl cellulose is uniformly dispersed in deionized water, stirred vigorously and methacrylic anhydride is added, then sodium hydroxide solution is injected into the mixture, stirred at room temperature for a certain period of time, the resulting suspension is heated to obtain a milky white colloidal precipitate, then placed in a dialysis bag for dialyzation, and freeze-dried to obtain methacrylated hydroxypropyl cellulose; (2) Preparation of precursor liquid: uniformly dispersing methacrylated hydroxypropyl cellulose, luminophore and photoinitiator in an organic solvent to obtain a precursor liquid having a certain methacrylated hydroxypropyl cellulose content; (3) Preparation of left-handed circularly polarized luminescent composite photonic film: After centrifuging the precursor liquid in step (2) to remove bubbles, take an appropriate amount and drop it on a substrate, place the substrate with the precursor liquid on the support of a spin coater to form a uniform film by spin coating, and then stand it in a dark place for more than 15 minutes to self-assemble to form a chiral nematic structure, then use ultraviolet light for cross-linking polymerization for at least 5 minutes, and then dry it to obtain a left-handed circularly polarized luminescent composite photonic film.
7. The preparation method according to claim 6, characterized in that: In the step (1), the ratio of hydroxypropyl cellulose to deionized water is 1 g:50 mL; the concentration of the sodium hydroxide solution is 5 mol·L ‒1 ; The mass ratio of hydroxypropyl cellulose, methacrylic anhydride and sodium hydroxide is 20.0:82.8:24.0; sodium hydroxide solution is injected into the mixture, stirred at room temperature for 12 hours, the resulting suspension is heated to 40-50°C and kept warm for 1 hour to obtain a milky white colloidal precipitate, and then placed in a dialysis bag with a molecular cutoff of 12000-14000 for dialyzing; and / or In step (2), the photoinitiator is a photoinitiator having active hydroxyl groups; the luminophore is an N-(3-(phenylamino)allylidene)aniline hydrochloride derivative; the organic solvent is N,N-dimethylformamide; the mass ratio of the methacrylated hydroxypropyl cellulose, the luminophore and the photoinitiator is 300-500:1:1; the content of the methacrylated hydroxypropyl cellulose in the precursor liquid is 68wt%-72wt%; and / or In step (3), the wavelength of the ultraviolet light is 365nm and the power is 5W.
8. The preparation method according to claim 7, characterized in that: The mass ratio of the methacrylated hydroxypropyl cellulose, the luminophore and the photoinitiator is 350-450:1:
1.
9. The preparation method according to claim 8, characterized in that: The mass ratio of the methacrylated hydroxypropyl cellulose, the luminophore and the photoinitiator is 380-420:1:
1.
10. The preparation method according to claim 6, characterized in that: In step (2), the luminophore is an N-(3-(phenylamino)allylidene)aniline hydrochloride derivative, and its preparation steps are as follows: 1,1,3,3-tetramethoxypropane is added to an anhydrous ethanol solution of 4-X aniline, and then an appropriate amount of 36wt% concentrated hydrochloric acid is slowly added dropwise, stirred at room temperature for a certain period of time, filtered, washed with anhydrous ethanol, and dried to obtain an N-(3-(phenylamino)allylidene)aniline hydrochloride derivative PA-X with fluorescent properties, where X is bromine, trifluoromethyl or phenyl.
11. The preparation method according to claim 10, characterized in that: The molar ratio of 1,1,3,3-tetramethoxypropane to 4-X aniline is 1:2; and / or The ratio of 1,1,3,3-tetramethoxypropane to concentrated hydrochloric acid is 1 mmol:1 mL; and / or Step (2) was stirred at room temperature for 5 hours.
12. The preparation method according to claim 7, characterized in that: The photoinitiator is 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone.
13. Use of the left-handed circularly polarized luminescent composite photonic film described in any one of claims 1 to 5 or the left-handed circularly polarized luminescent composite photonic film prepared by the method described in any one of claims 6 to 12 in anti-counterfeiting pattern labels.
Citation Information
Patent Citations
Structural color film and preparation method thereof
CN116731357A
Cellulose structural color hydrogel and preparation method thereof
CN117050250A